PEMANFAATAN LIMBAH KAYU GELAM (Melaleuca cajuputi) dan SERBUK ULIN (Eusideroxylon zwageri) SERTA SERBUK CAMPURAN UNTUK PEMBUATAN PAPAN SEMEN PARTIKEL - Brave Sugesty Tampubolon (Jurnal Sylva Scienteae, 2020)
This study aims to give a scientific information about physical character of cement board particle from the waste of Gelam powder, the waste of Ulin Powder and the mixed waste from Gelam Powder and Ulin Powder. The need for new breakthrough in knowledge in the field of biocomposite. One of the potentially developed from biocomposite products is cement board particle. Testing of physical character on cement boards particle includes testing of density, water content or moisture content, water absorption, and heavy development. In the density test showed the highest average value was found on the cement board particle using mixture Gelam powder with Ulin powder with the ratio 50% : 150% between powder and adhesive, with a value 1.56 cm3/gr. The water content test showed the highest avarage value was found on the cement board particle using Gelam Powder with the ratio 50% : 150% between powder and adhesive with a value 14.00%. in the water absorption test showed the highest avarage value was found on the cement board particle using Gelam powder with ratio 50% : 50% between serbuk and adhesive with value 51.93%. In heavy development the highest avarage value was found on the cement board particle using Gelam powder with ratio 50% : 50% between serbuk and adhesive with value 3.94%.The results of density testing, water content testing, water absorption testing and heavy development testing show that the cement board particle heavy expansion testing show that the cement board particle has fulfilled SNI 2006 standard. Keywords: cement board particle; Gelam; Ulin; Density; Water Content; Water Absorption; Heavy development; and SNI 2006